Optimization of Selection Suppliers for Rice Raw Material Using AHP (Analytical Hierarchy Processes) and TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) Methods in CV Gembira - Prasetya, Adi Tulus; Donoriyanto, Dwi Sukma (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
CV Gembira is engaged in the production of Rice Mill with the trademark Osing Rice, and has 3 variants, namely Osing Super, Osing Premium and Osing Gold. Problems CV Gembira one of them is the delay in the delivery of rice raw materials carried out by supplier and also the quality of goods that do not meet the criteria. The AHP method is the preferred method. There are several reasons, namely, AHP provides a hierarchical representation of a problem that is useful in assisting decision making. The selection of the TOPSIS method as an auxiliary method is based on simple logic and has the farthest distance to the negative ideal solution. After performing calculations using the AHP and TOPSIS methods, alternative sequence results are obtained supplier the best that can be used by CV Gembira with a preference value of 0.6249 is owned by UD Bintang Timur.